PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI SDN 001 KEMPAS JAYA - Sumini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article provides an overview of students’ activities and learning outcomes through Make a Match as a cooperative learning method. Make a Match is a type of cooperative learning model that contains elements of fun games for students. It can produce learning activities while playing. The research used was Classroom Action Research (CAR) using a research design model Kemmis and Mc. Taggart. The research was conducted at SDN 001 Kempas Jaya. The population of research involved 26 fourth-grade students, which consisted of 18 male and 8 female students. The research used quantitative data analysis. Descriptive statistical data collection techniques were implemented through observations, interviews, and evaluation tests at the end of the cycle. In the pre-cycle, the criteria for students’ activity were 38.46%. After applying the Make a Match cooperative learning model, the result showed an increase. In cycle 1, the criteria for students’ activity were 73.07% and in cycle 2, the students’ activity was 92.30%, which was active in following the learning process. The result of students’ learning outcomes in the pre-cycle obtained completeness of 42.30% with an average value of 68.84. In cycle 1, the completeness was 76.92% with an average of 75.57. In cycle II, students’ learning completeness increased to 92.30% with an average of 82.50. Based on the results of research, students’ learning activities were increasingly improved every cycle.